The challenge of emerging technologies for effective corporate governance in the digital age - Mohd Rodzi, Nor Kartini; Ramlee, Roslida; Naiimi, Nazirah; Ieamwijam, Rugkita (Faculty of Accountancy, 2025)
Corporate governance is a central and dynamic aspect of business. The term 'governance' is derived from the Latin word 'gubemare', which means to steer, often in the context of navigating a ship. The term suggests that corporate governance encompasses the function of direction rather than mere control. One of the most widely accepted definitions is provided by the Organisation for Economic Co-operation and Development (OECD), which describes corporate governance as the process of directing company operations and managing relationships between shareholders and stakeholders (OECD, 2004). Effective corporate governance fosters trust, transparency, and accountability. This, in tum, encourages long-term investment, promotes sustainable economic growth, and ensures financial stability. It ensures that companies are managed responsibly, aligning their actions with the interests of stakeholders.